Pendampingan Guru SD dalam Mengembangkan Pembelajaran Bahasa Indonesia Berbasis Literasi Kritis di UPTD SDI Sikumana 3 - Markus Sampe; Taty R. Koroh; Habibi Musa; Monica Bellandina Abolla (Prodi PGSD Unsultra, 2026)
Indonesian language learning in elementary schools aims not only to improve reading and writing skills but also to foster critical thinking and in-depth literacy skills. Critical literacy enables students to systematically analyze, evaluate, and express opinions based on the texts they read. This study aims to assist teachers at SDI Sikumana 3 in developing critical literacy-based Indonesian language learning to improve the quality of teaching and students' literacy skills. The method used was Community Service (PkM) with a participatory approach. Activities were carried out through workshops, direct classroom mentoring, and evaluation of learning planning and implementation. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively. The results of the activities showed an increase in teachers' understanding of the concept of critical literacy, their ability to design literacy-based learning activities, and the application of critical reading and reflective writing strategies in the classroom. Teachers were able to facilitate students' questions, analyze information, and express opinions in writing and orally. This activity also encouraged the creation of a literacy culture in schools, including the use of storybooks, digital media, and group discussions. Based on these findings, critical literacy-based teacher mentoring effectively improves the quality of Indonesian language learning at the elementary school level. Recommendations from this activity include the need for sustainable programs, school management support, and the integration of critical literacy into the elementary school curriculum to ensure more contextual, critical, and creative learning.